GAMBARAN UPAYA MENGATASI KECEMASAN PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - Ni Wayan Purnami; V.M.E Sri Purwadmi Rahayu; I Ketut Dira; Putu Intan Daryaswanti (Sekolah Tinggi Ilmu Kesehatan Kesdam IX/Udayana, 2019)
Background: Chronic kidney disease is a progressive and irreversible renal function disorder in which the body's ability to fail to maintain the metabolism and balance of fluids and electrolytes causes uremia. One medicine for the treatment of chronic kidney failure is hemodialysis therapy. Ironically, many patients undergoing hemodialysis experience anxiety. This study aims to determine the efforts to overcome the anxiety of chronic kidney failure in patients undergoing hemodialysis in the Hemodialysis Room of Sanglah Hospital, Denpasar. Method: The research design used was a descriptive analysis approach survey. The study sample used was kidney failure patients who experienced chronic hemodialysis anxiety and light using consecutive sampling technique. Data obtained in April 2012 by filling out a questionnaire about efforts to overcome data analysis anxiety in univariate. Results: Of the 40 respondents who underwent hemodialysis, there were 28 people (70%) experiencing moderate anxiety and 12 people (30%) experiencing mild anxiety. And to overcome anxiety is 27 people (67.50%) doing cognitive therapy and 13 people (32.50) doing relaxation techniques. Conclusions: Some efforts made such as cognitive therapy and relaxation techniques can reduce anxiety in patients with chronic renal failure undergoing hemodialysis.Keywords : Chronic Kidney Failur; Hemodialysis; Fear